Fluid Management in Acute Respiratory Distress Syndrome - Casey, Jonathan D.; Semler, Matthew W.; Rice, Todd W. (Seminars in Respiratory and Critical Care Medicine, 2019)
One of the defining features of acute respiratory distress syndrome (ARDS) is noncardiogenic pulmonary edema, resulting from increased permeability of the alveolar–capillary barrier and passage of protein-rich fluid into the interstitium and alveolar spaces. The loss of protein from the intravascular space disrupts the normal oncotic pressure differential and causes patients with ARDS to be particularly sensitive to the hydrostatic forces that correlate with intravascular volume. Conservative fluid management, in which diuretics are administered and intravenous fluid administration is minimized, may decrease hydrostatic pressure and increase serum oncotic pressure, potentially limiting the development of pulmonary edema. However, the cause of death in most patients with ARDS is multiorgan system failure, not hypoxemia, and the impact of conservative fluid management on the incidence of extrapulmonary organ failure during ARDS is unclear. These physiologic observations have led to a series of studies examining the impact of fluid management on the development of, resolution of, survival from, and long-term outcomes from ARDS. While questions remain, the current literature makes it clear that fluid management is an integral part of the care of patients with ARDS.
Keywords: acute respiratory distress syndrome; pulmonary edema; hydrostatic pressure; conservative fluid management